Minimizing beneficiation wastewater through internal reuse of process water in flotation circuit. (1st February 2020) - Lin, Shangyong; Liu, Runqing; Wu, Meirong; Hu, Yuehua; Sun, Wei; Shi, Zhizhong; Han, Haisheng; Li, Wenheng
Abstract: Cost-effective methods for reducing freshwater requirement and wastewater emission in beneficiation processes (particularly in flotation process) are greatly important in the modern mining industry. This study aims to minimize water consumption and wastewater generation in dressing plants by internally reusing process water at certain stages of flotation circuit. Laboratory scale tests demonstrated that locked cycle recycling of process water built up chemical reagents in water, which in turn influenced the flotation performance of valuable minerals and significantly decreased the grade and recovery of concentrates. Changing flotation reagent regimes in response to flotation fluctuations can reliably and feasibly maintain mineral recovery efficiency during the reuse process. Industrial scale tests validated that the quality of concentrates obtained with and without process water reuse did not show any considerable difference and satisfied the product specifications by carefully adjusting the dosage of flotation reagent. The required reagent dosages in the flotation circuit were reduced by more than 10% after using recycled water. Among the required reagent dosages, sodium sulfide (Na2 S) was sharply reduced by 18.56%. Most importantly, the internal reuse of process water in the flotation circuit minimized freshwater consumption by 34.62% (i.e., from 5.2 t/d to 3.4 t/d), indicating that 525.6 tons of wastewater would no longer be generated every year. Overall, the proposed internal reuse process is a cost-effective and eco-friendly alternative for greening flotation process. Graphical abstract: Image 10173 Highlights: Internal reuse of process water in the flotation process is feasible and reliable. Changing reagent suite reduces the negative effect of process water on flotation. Internal reuse of process water minimized water consumed and wastewater emission. Internal reuse of process water promotes the reutilization of chemical reagents.